PENDAMPINGAN PEMERIKSAAN KESEHATAN MATA GRATIS SEBAGAI UPAYA DETEKSI DINI PADA LANSIA DI RINGINSARI KULON - Nunik Zuhriyah M.Pd.I; M Zunaidul Muhaimin; Imam Achmad Alvinnas (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2026)
The elderly are a vulnerable group who are at high risk of vision impairment due to degenerative processes, limited access to health services, and low awareness of the importance of regular eye examinations. This condition is also found among the elderly in Ringinsari Kulon Village, most of whom have never received regular eye examinations. This community service activity aimed to provide free eye examinations as an effort to detect early vision impairment in the elderly, while also raising public awareness of the importance of eye health in old age. The method used was a participatory approach (PAR) through visual acuity tests, initial screening for eye disorders, and eye health education, which was carried out collaboratively with village officials and local health workers. The results of the activity showed that most of the elderly participants experienced a decline in visual acuity that had not been optimally treated, either due to economic factors or lack of information. Through this assistance program, seniors receive initial eye examinations, referrals for further treatment for those who need it, and a better understanding of eye health prevention and care. This program has had a positive impact on increasing awareness among seniors and their families about maintaining eye health and encouraging a culture of regular eye examinations.